CD161 expression on hepatitis C virus-specific CD8+ T cells suggests a distinct pathway of T cell differentiation. - Northfield, J; Kasprowicz, V; Lucas, M; Kersting, N; Bengsch, B; Bengsh, B; Kim, A; Phillips, R; Walker, B; Thimme, R; Lauer, G; Klenerman, P (2008)
UNLABELLED: Hepatitis C virus (HCV) causes chronic infection accompanied by a high risk of liver failure and hepatocellular carcinoma. CD8+ T cell responses are important in the control of viremia. However, the T cell response in chronic infection is weak both in absolute numbers and in the range of epitopes targeted. In order to explore the biology of this response further, we analyzed expression of a panel of natural killer cell markers in HCV compared with other virus-specific T cell populations as defined by major histocompatibility complex class I tetramers. We found that CD161 was significantly expressed on HCV-specific cells (median 16.8%) but not on CD8+ T cells specific for human immunodeficiency virus (3.3%), cytomegalovirus (3.4%), or influenza (3.4%). Expression was seen in acute, chronic, and resolved disease and was greatest on intrahepatic HCV-specific T cells (median 57.6%; P < 0.05). Expression of CD161 was also found on hepatitis B virus-specific CD8+ T cells. In general, CD161+CD8+ T cells were found to be CCR7- "effector memory" T cells that could produce proinflammatory cytokines (interferon-gamma and tumor necrosis factor-alpha) but contained scanty amounts of cytolytic molecules (granzyme B and perforin) and proliferated poorly in vitro. Expression of CD161 on CD8+ T cells was tightly linked to that of CXCR6, a chemokine with a major role in liver homing. CONCLUSION: We propose that expression of CD161 indicates a unique pattern of T cell differentiation that might help elucidate the mechanisms of HCV immunity and pathogenesis.